Working while unwell: Workplace impairment in people with severe asthma. Issue 6 (17th May 2018) - Hiles, S. A.; Harvey, E. S.; McDonald, V. M.; Peters, M.; Bardin, P.; Reynolds, P. N.; Upham, J. W.; Baraket, M.; Bhikoo, Z.; Bowden, J.; Brockway, B.; Chung, L. P.; et al.
Summary: Background: Severe asthma affects quality of life; however, its impact on workplace productivity is poorly understood. Objective: To compare workplace productivity—absenteeism and presenteeism—and impairment in daily activities in severe and non‐severe asthma over time and identify characteristics associated with presenteeism in severe asthma. Methods: The Severe Asthma Web‐based Database is an ongoing observational registry from Australia, New Zealand and Singapore. At April 2017, 434 patients with severe asthma and 102 with non‐severe asthma were enrolled (18‐88 years; 59% female). Participants provided comprehensive clinical and questionnaire data at baseline and were followed‐up every 6 months for 24 months. Absenteeism (percentage of time not at work), presenteeism (self‐reported impairment at work) and impairment in daily activities outside work due to health problems in the last week were calculated. Results: At baseline, 61.4% of participants with severe asthma and 66.2% with non‐severe asthma under 65 years were employed. At younger ages (30‐50 years), fewer severe asthma participants were employed (69% vs 100%). Presenteeism and impairment in daily activity were more frequently reported in severe asthma and in participants with poorer asthma control, poorer lung function and more past‐year exacerbations ( P  <   .01). Over time, deteriorating asthma control was associated with increasing presenteeism. Although absenteeism was not different between severe and non‐severe asthma, worse asthma control was associated with absenteeism ( P  <   .001). In participants with severe asthma, presenteeism was reported more frequently in those with poorer asthma control, poorer asthma‐related quality of life and symptoms of depression or anxiety ( P  <   .01). Conclusion and clinical relevance: Severe asthma was associated with impairment at work and outside the workplace. Improving asthma control and mental health may be important targets for optimizing workplace productivity in severe asthma. Presenteeism and absenteeism may represent key metrics for assessing intervention efficacy in people with severe asthma of working age.